IDENTIFIKASI LANSEKAP BERSEJARAH DI KECAMATAN KAIDIPANG KABUPATEN BOLAANG MONGONDOW UTARA - Petrik Runtuwene; Cynthia E. V. Wuisang; Alvin J. Tinangon (Department of Architecture, Engineering Faculty - Sam Ratulangi University, 2021)
The historical event is a journey of the nation starting from the era of the Hindu, Buddhist and Islamic style kingdoms, to the era of European colonization. The arrival of foreign nations in the past has left many sites and areas of cultural and historical value as valuable assets that describe people's lives in the past. Based on its history, the Great Kaidipang kingdom was a combination of the Kaidipang kingdom and the Bolangitang kingdom. The residential area of the Kaidipang community still maintains its customs. However, the Kaidipang sub-district experienced a change in the cultural landscape due to the changing times. The purpose of this study was to identify historical landscapes in Kaidipang District, North Bolaang Mongondow Regency and analyze the characteristics of historical landscapes in Kaidipang District, Bolaang Mongondow Regency. The method used in this research is descriptive qualitative by collecting historical landscape data in Kaidipang District. Descriptive analysis was conducted to determine the characteristics of the historical landscape in the study area. The results of this study indicate that settlements in Kaidipang District follow the same pattern as the royal era under the leadership of King Sam Suit Pontoh which is divided into 2, namely the northern region and the southern region where these two areas also have the same landscape, namely linear (settlement pattern follows the road). . The residential area used to be divided into 2, namely residential areas and agricultural areas, but with the expansion of the North Bolaang Mongondow Regency, land conversion occurred so that the distribution of the community tends to the north and south areas. The cultural landscape of the Kaidipang community has its own characteristics related to traditions, settlement culture, and landscape order. The analysis carried out on eleven components of the formation of the cultural landscape characteristics of the Kaidipang Community is a type of landscape character that is still traditional and life relies on the surrounding natural environment and agricultural products. The life of the people still upholds the values of tradition and culture that are still practiced.